Multiple Faces of Chronic Lymphocytic Leukaemia: A Patient with Renal, Cardiac, and Skeletal Complications - Zay Myo Htet; Cesar Gomez; Ahsan Ali; Sunil Nair; Mahzuz Karim (Case Reports in Nephrology)
We describe a patient who had chronic lymphocytic leukaemia (CLL) Binet stage A at presentation with further evidence of disease at multiple sites but who initially required no treatment. However, several years later, her peripheral blood lymphocyte count started to increase, and soon after that she suffered an acute myocardial infarct (in the absence of coronary atheroma) together with proteinuric renal failure due to membranoproliferative glomerulonephritis. Her renal function improved markedly following anti-CLL chemotherapy. We postulate that her cardiac and renal disease were both complications of her CLL. In patients with CLL who develop new clinical signs or symptoms (even if apparently unrelated), consideration should be given as to whether these may be disease complications as this may serve as an indication to commence anti-CLL therapy; close liaison between different specialties is vital.